Prosthodontic rehabilitation for maxillofacial defects by mucormycosis post Covid-19 pandemic - Fitrian Riksavianti; Ike Damayanti Habar (Indonesian Journal of Prosthodontic, 2023)
Since the outbreak of Covid-19, with every mutation, it has posed various challenges to human life and in health sciences. Patients on corticosteroids or with comorbidities like diabetes mellitus are at increased risk of post Covid-19 infections like mucormycosis. Mucormycosis is a rare opportunistic infection, often associated with immunocom-promised states. Fungal invasion of the hard palate, paranasal sinuses, orbits and brain is the commonest form of rhinocerebral mucormycosis. Among the medical professionals involved in managing patients with mucormycosis, maxillofacial prosthodontists are responsible for prosthetic treatment of lost oral and maxillofacial structures, help-ing patients to socialize and have an acceptable quality of life after surgical treatment. This literature review is aimed to describe maxillofacial prosthodontist challenge in rehabilitation of mucormycosis post Covid-19 infection. It is concluded that prosthodontist face many challenges in mucormycosis rehabilitation. Prosthodontist should be ca-pable to early detection and diagnosis, carefull in planning and designing the prosthesis, wise in using of softliner material, and should always maintain long-term follow-up if any sign of lesion recurrence.